Don't be a stranger - Nesbitt, John D. (Five Star, A part of Gale, Cengage Learning, 2015)
"Elwood Lawrence--top hand at the Crown Butte ranch--tries to find out where the cattle are disappearing to. It looks like an inside job. His work becomes complicated when he develops an interest in a woman who comes to visit the ranch and behind it all is the disappearance of a flashy stranger who is said to be a bank robber"--Amazon.com.